2001
DOI: 10.1016/s0008-6363(00)00199-1
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular administration of estrogen may promote angiogenesis and perfusion in a rabbit model of chronic limb ischemia

Abstract: Administration of estrogen promotes angiogenesis and perfusion in ischemic rabbit hindlimbs. Thus, estrogen may represent a new therapeutic modality in the management of arterial insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…Indeed, in the animal model used in the present study, fractured bones were healed in most of the animals by day 72. Although estrogen has been shown to stimulate angiogenesis in skeletal muscles (Kyriakides et al 2001), we observed a slight increase in capillary density in D and 4-MBC treated rats, but not in the estrogen supplemented animals after 36 days of fracture healing. On the other hand, the estrogenic effect of the substances may facilitate the animals to restore their physical activity more rapidly.…”
Section: Analyses Of Musclecontrasting
confidence: 81%
See 1 more Smart Citation
“…Indeed, in the animal model used in the present study, fractured bones were healed in most of the animals by day 72. Although estrogen has been shown to stimulate angiogenesis in skeletal muscles (Kyriakides et al 2001), we observed a slight increase in capillary density in D and 4-MBC treated rats, but not in the estrogen supplemented animals after 36 days of fracture healing. On the other hand, the estrogenic effect of the substances may facilitate the animals to restore their physical activity more rapidly.…”
Section: Analyses Of Musclecontrasting
confidence: 81%
“…In muscles of mature female rodents, estrogen has been associated with modulation of muscle fiber types (Kadi et al 2002, Feng et al 2004, whereas, the crosssectional areas of all types of fibers were not affected by estrogen status (McClung et al 2006, Moran et al 2007. Moreover, estrogen has been reported to promote angiogenesis in skeletal muscles of estrogen deficient animals (Kyriakides et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…8 Estrogen enhances endothelial cell activities in vitro 1,9 and has favorable effects on ischemic neovascularization in vivo. 10,11 In human studies, it was reported that postmenopausal hormone replacement therapy was associated with reduced risk of mortality after myocardial infarction (MI). 12 Tissue ischemia induces upregulation of angiogenic growth factors and mobilization of circulating cellular elements that together enable development of an accessory vasculature for organ survival.…”
Section: Editorial P 2203 Clinical Perspective P 2270mentioning
confidence: 99%
“…7 A candidate mechanism of cerebral protection is the ability of E2 to modulate angiogenesis. 8 -11 E2-mediated angiogenesis occurs in normal tissues (eg, female reproductive tract 8,9,12 , retina, 10 and other nonreproductive tissues) 11 as well as pathologic conditions (eg, experimental limb ischemia, 13 tumors, 8 and aging brain). 14 Enhancement of angiogenesis is an attractive property.…”
mentioning
confidence: 99%